Effect of NSPase Supplementation in Wheat Containing Diet on Performance, Digesta Viscosity and Apparent Metabolizable Energy of Broiler - Saeton, Wanida; Jitviriyanon, Surapan; Songserm, Ornprapun; Ruangpanit, Yuwares (Journal of Mahanakorn Veterinary Medicine, 2021)
This study was to evaluate the effects of NSPase supplementation in wheat containing diet on performance, digesta viscosity and apparent metabolizable energy (AME) of broilers. A total of 2,000 1-day-old Ross 308 1,000 males and 1,000 female broiler chicks using completely randomized design (CRD) divided into 5 treatments 8 replicates with 50 birds each. The Broilers fed 5 dietary treatments, the control diet (PC), the control diet with 150 kcal/kg ME reduction (NC) and the NC diet supplemented with NSPase A, B and C (NC+NSPase A, B and C). The results of the study throughout 1-37 days, the PC group had better FCR than that of NC and NC+NSPase C group (P<0.05). But the supplementation of NSPase A and B help to improve FCR as good as that of the PC group. There was no significant difference of feed intake, body weight gain and mortality among dietary treatments throughout the experimental period, but 1-17 days of age feed intake in NC group and NC+NSPase A and C higher the PC group. However, the supplementation of NSPase reduced the jejunum digesta viscosity (P<0.05), but there was no significant difference in ileum digesta viscosity (P>0.05). The AME and AMEn in the NC group were lower than that of the PC group (P<0.01) and when supplementing NSPase A, B and C increased AME and AMEn but was lower than that of the PC group.